An Unusual Cause of Dysphonia with Hemoptysis: A Laryngeal Live Leech - Mohsen Rajati; Shirin Irani; Ehsan Khadivi; Mehdi Bakhshaee (Iranian Journal of Otorhinolaryngology, 2014)
Introduction: Foreign bodies in the upper airway are one of the most challenging otolaryngology emergencies and have various presentations depending on their physical properties and location. Leeches are blood-sucking hermaphroditic worms that vary in color, length, and shape. They usually reside in fresh-water streams and lakes. When rural untreated water is drunk, leeches may localize in the nose, pharynx, and esophagus, or rarely in the larynx. CaseReport: This case is a man who was referred to our otolaryngology clinic with a complaint of hemoptysis and mild respiratory distress. The patient’s symptoms were all relieved post operatively and he was discharged on the second day following the procedure.     Conclusion: Leeches should be suspected as an airway foreign body in patients with a recent history of drinking stream water.